Obesity Is Associated with Higher Oxidative Stress Among PLWH and Healthy Men, But Not Women, in the Miami Adult Studies on HIV (MASH) Cohort. (29th May 2020) - Rodriguez, Jose Bastida; Hernandez, Jacqueline; Teeman, Colby; Huang, Yongjun; Gonzalez, Nicholas; Martinez, Sabrina Sales; Campa, Adriana; Seminario, Leslie; Jasmin, Jupshy; Tamargo, Javier; Johnson, Angelique; Baum, Marianna
Abstract: Objectives: Over-expression of oxidative stress leads to the development of obesity-related complications, including non-communicable diseases in healthy populations. We determined the association between obesity and oxidative stress in people living with HIV (PLWH) and un-infected, healthy individuals. Methods: Participants were selected from the MASH cohort. Demographics, anthropometrics, bioimpedance analysis, and fasted blood samples were collected by trained personnel. HIV Viral Load (VL, copies/ml) was abstracted from medical charts. Oxidative stress was determined using ARBOR ASSAYS (Ann Arbor, MI) glutathione colorimetric detection kit. Descriptive statistics were used to analyze demographics, HIV status, VL (undetectable VL < 50copies/ml), and obesity (BMI ≥30 kg/m2; body fat % >25 Males and >35 Females) status. Logistic regression was used to find an association between high oxidative stress (% oxidized glutathione [GSSG] defined as % GSSG above the median) and obesity (BMI) in the group of PLWH and the healthy group. Association between body fat %, and high % GSSG was also determined. Linear regression was used to find the association between % GSSG and BMI. Results: Participants' mean age was 54.4 ± 7.4 years (n = 738), 55.3% were male and 66.3% Black; 46.7% were PLWH; 90.9% had an undetectable viral load and 47.3% of all participants were obese. A univariate linear regression showed a positive association between BMI and % GSSG among the PLWH (b = 0.066 SE = 0.032, CI: 0.002–0.129; P = 0.043) but not in the healthy group. Logistic regression showed obesity to be a significant predictor for high % GSSG (OR = 1.42, 95% CI:1.06–1.92; P = 0.019) after controlling for age, gender and HIV status. However, when participants were separated by sex, obese male participants were 1.55 times more likely to have high % GSSG (OR = 1.55, 95% CI: 1.025–2.348; P = 0.038) than non-obese males after controlling for age and HIV status. Statistically significant associations were not observed in females, regardless of HIV status. Conclusions: Obese PLWH and obese healthy participants were more likely to have high oxidative stress than non-obese participants. The increased oxidative stress in males but not in females may provide one of the mechanisms for increased risk for non-communicable diseases such as cardiovascular disease, in males. Funding Sources: National Institute on Drug Abuse.